Genomic Research and Wide Data Sharing: Views of Prospective Participants - Trinidad, Susan Brown (2010)
PURPOSE: Sharing study data within the research community generates tension between two important goods: promoting scientific goals and protecting the privacy interests of study participants. The present study was designed to explore the perceptions, beliefs, and attitudes of research participants and possible future participants regarding genome-wide association studies (GWAS) and repository-based research. METHODS: Focus group sessions with (1) current research participants, (2) surrogate decision-makers, and (3) three age-defined cohorts (18–34 years, 35–50, >50). RESULTS: Participants expressed a variety of opinions about the acceptability of wide sharing of genetic and phenotypic information for research purposes through large, publicly accessible data repositories. Most believed that making de-identified study data available to the research community is a social good that should be pursued. Privacy and confidentiality concerns were common, though they would not necessarily preclude participation. Many participants voiced reservations about sharing data with for-profit organizations. CONCLUSIONS: Trust is central in participants’ views regarding GWAS data sharing. Further research is needed to develop governance models that enact the values of stewardship.